1999
DOI: 10.1021/ja9930317
|View full text |Cite
|
Sign up to set email alerts
|

Retention of the Cis Proline Conformation in Tripeptide Fragments of Bovine Pancreatic Ribonuclease A Containing a Non-natural Proline Analogue, 5,5-Dimethylproline

Abstract: Attention is focused on L-5,5-dimethylproline (dmP) as a substitute to lock L-proline (Pro) in a cis conformation in peptides and proteins, to prevent cis/trans isomerization when a protein with cis X-Pro peptide groups unfolds. Procedures have been developed to obtain optically pure L-dmP and to incorporate this sterically hindered residue as the central one in tripeptides that are suitable for fragment coupling to prepare synthetic proteins. Based on the sequences of residues 92-94 (Tyr-Pro-Asn:YPN) and 113-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
91
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 101 publications
(94 citation statements)
references
References 63 publications
3
91
0
Order By: Relevance
“…The nonnative proline isomers that also diminished the initial collapse may exert their effect in a similar manner. NMR investigations showed that a peptide fragment of RNase A forms a turn with a cis-Pro-93 but not with a trans-Pro-93 (20,47). Thus, the entropy of the polypeptide chain is higher in U eq than in U vf .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The nonnative proline isomers that also diminished the initial collapse may exert their effect in a similar manner. NMR investigations showed that a peptide fragment of RNase A forms a turn with a cis-Pro-93 but not with a trans-Pro-93 (20,47). Thus, the entropy of the polypeptide chain is higher in U eq than in U vf .…”
Section: Discussionmentioning
confidence: 99%
“…However, in contrast to the folded protein, an X-Pro peptide group is in equilibrium between the cis and trans forms in peptides and denatured proteins. To obtain a better estimation of the expected initial values of U vf in double-jump kinetic experiments, we explored a tripeptide, WdmPN, which contains a proline analog, dimethyl proline (dmP) (20). This analog overwhelmingly forms a cis X-Pro peptide group in peptides with the same backbone and side-chain conformations as regular cis prolines do, and this makes it a good model peptide for a cis Trp-Pro peptide group (20).…”
mentioning
confidence: 99%
“…43 Results of NMR investigations indicated that a peptide fragment of RNase A forms a turn with Pro93 in a cis form but not in a trans form. 44,45 Consequently, it is reasonable that the fraction of sample containing the cis proline remains in an expanded state even under the solution condition that favors folding.…”
Section: Cis-trans Isomerization In the Folding Of Barnasementioning
confidence: 99%
“…35 Indeed by replacing Pro114 of RNase A with 5,5-dimethyl-L-proline, which is known to form almost exclusively cis prolyl isomers, 37 both the protein stability and the rate of refolding were significantly enhanced. 38 Similarly, 4-fluoroproline residues are known to markedly affect the stability of cis and trans peptide bonds.…”
Section: Synthesis and Structures Of The (4r)-and (4s)-fpro24 Analogumentioning
confidence: 99%